THE CHALLENGES OF ISLAMIC EDUCATION IN A GLOBAL CONTEXT - Rahman, Yudi Ardian (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2023)
Globalization is a complex phenomenon that has had far-reaching effects. Not surprisingly, the term,